Framework for inculcating Islamic values through problem solving in mathematics and lesson study approach - Khalid, Madihah (IIUM Press, 2017)
The purpose of this paper is to relate the development of a framework for inculcating Islamic values among elementary school children. The teaching of Islamic values is to be integrated in the teaching of mathematics problem solving. Meanwhile, lesson study have been identified as the best professional development strategy for the purpose of coaching the teachers to teach effectively. The paper discusses the importance of upholding Islamic values in the current time and looks at the opportunities for value inculcation across the curriculum in particular for the subject of mathematics. The framework developed is represented by three layers of concentric circles. In the innermost circle, Islamic values are separated into three aspects, akhlaq, adab and virtues from the sunnah of the prophet. Subsequently, the second inner circle comprises four components of problem solving i.e. thinking and reasoning, communication, collaboration and attitude. These elements have been selected as important elements to inculcate values. Finally, lesson study, comprising plan, teach and reflect phases have been chosen as a medium to coach teachers to the processes identified and mentioned in the outermost circle. Muslim scholars’ views, and their theories on education and writings on values and character traits, have also been considered in developing the framework. The tradition of the Muslim mathematicians during the Islamic civilization is also included.